2013
DOI: 10.1130/g33752.1
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of ultrahigh-temperature metamorphism in the Acadian orogen, Connecticut, USA

Abstract: Connecticut, USA Discovery of ultrahigh-temperature metamorphism in the Acadian orogen, Email alerting services articles cite this article to receive free e-mail alerts when new www.gsapubs.org/cgi/alerts click Subscribe to subscribe to Geology www.gsapubs.org/subscriptions/ click Permission request to contact GSA http://www.geosociety.org/pubs/copyrt.htm#gsa click official positions of the Society. citizenship, gender, religion, or political viewpoint. Opinions presented in this publication do not reflect pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 39 publications
5
37
0
Order By: Relevance
“…This study investigates halos of rutile needles (or plates) with or without apatite inclusions surrounding ruptured fluid inclusions or inferred former coesite inclusions in garnet. We focus on two localities: (i) UHT metapelitic gneisses within the southern end of the CMT in northeastern CT, USA (Ague & Eckert, ; Ague et al ., ) and (ii) diamondiferous saidenbachite from the Saxonian Erzgebirge (Massonne, ). Halos from both localities have rutile needles and/or plates; apatite coexists with rutile in the Erzgebirge rocks (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates halos of rutile needles (or plates) with or without apatite inclusions surrounding ruptured fluid inclusions or inferred former coesite inclusions in garnet. We focus on two localities: (i) UHT metapelitic gneisses within the southern end of the CMT in northeastern CT, USA (Ague & Eckert, ; Ague et al ., ) and (ii) diamondiferous saidenbachite from the Saxonian Erzgebirge (Massonne, ). Halos from both localities have rutile needles and/or plates; apatite coexists with rutile in the Erzgebirge rocks (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…S7 and Materials and Methods). These minerals are well known from UHT and/or HPG rocks at the locality (24)(25)(26), so their absence in the rocks of this study suggests matrix equilibration at UHP conditions in excess of about 3 GPa. This pressure result holds for a wide range of H 2 O activities and even at minimum is still ~2.6 GPa ( fig.…”
Section: Pseudosection Resultsmentioning
confidence: 65%
“…We study ~1050°C garnet-sillimanite-K-feldspar-biotite-quartz gneiss from the Brimfield Schist HPG-UHT field area (24,25), located within one of several westward-dipping thrust fault-bound slices in the southern CMT. The rocks are highly aluminous (up to ~40 vol% garnet and ~30 vol% Al 2 SiO 5 ) and are inferred to have metasedimentary, likely metapelitic, protoliths.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…to 500 Ma) systems (Brown, 2006(Brown, , 2007(Brown, , 2014 and, therefore, are important for understanding the geodynamic process in the early Earth, such as the rheological behaviour of the crust (Lund, Piazolo, & Harley, 2006), crustal growth and differentiation (Sawyer, Cesare, & Brown, 2011), and the heat source or tectonic settings for such extreme temperatures (Ague, Eckert, Chu, Baxter, & Chamberlain, 2013;Brown, 2007Brown, , 2014Clark, Fitzsimons, Healy, & Harley, 2011;Harley, 2008;Kelsey & Hand, 2015;Lund et al, 2006;Sawyer et al, 2011). Recent studies have confirmed that metamorphic temperatures >1,000°C are indeed obtainable, based on multiple thermobarometric methods (Korhonen, Clark, Brown, & Taylor, 2014;Mitchell & Harley, 2017), and have demonstrated that some pelitic granulites without the diagnostic mineral assemblages of UHT metamorphism also experienced these conditions based on ternary feldspar, Zr-in-rutile, Ti-in-zircon thermometry, and phase equilibria modelling (Ague et al, 2013;Gou, Zhang, Zhang, & Wang, 2014;Jiao, Guo, Mao, & Zhao, 2011;Li & Wei, 2016;Liu et al, 2012). These recent studies lead us to reevaluate some high-grade metamorphic complexes in the Khondalite Belt in the North China Craton (NCC) to confirm whether the metamorphism reached UHT conditions and to clarify the geodynamic implications.…”
mentioning
confidence: 99%